Public Transport Choice Behaviour in Thimi Bhaktapur - Prajapati, Sarita; Shrestha, Pradeep Kumar (Journal of Science and Engineering, 2020)
The public transport users tend to shift public transport mode in search of a better one. The choice depends on the various attributes of public transport, such as travel time, waiting time, comfort, safety, etc. Since there were competition among different public modes, such as buses, minibuses, microbuses, and even three-wheeler (tempo), the sustainability of the public transport directly depends on the public or users. The users continue to use those public transport which meet their expected level of service. This study focuses on examining attributes of different public transport alternatives available, investigating factors affecting preference of public transport alternatives and developing choice model for public transport alternatives. Multinomial logistic model was developed from the SPSS to find the probability of selecting particular public transport. The public transport choice among the four alternatives, whose destination was same, was found to be influenced by the variables, such as monthly income, age, travel time, walking time, waiting time, fare and gender. The model helps to understand the choice behavior of traveler and can be used for transport planning in future.